Contesting the feminist paradigm in Tsitsi Dangarembga’s texts: an africana womanist reading of She no longer weeps, nervous conditions and the book of not - Nkiwane, Sihle (Midlands State University, 2014)
Most often, Tsitsi Dangaremga is referred to as a feminist writer. Her works have been categorized as written in a feminist tradition. This research seeks to contest the notion that she is a feminist writer and that her works are feminist. Rather than having her texts read from a Feminist perspective, this study intends to read Dangarembga’s works from an Africana Womanist perspective. This research will show that the African woman does not view her male counterpart as the enemy, but as a victim as well, echoing the co-existence of the male and the female, the existence of healthy families, genuine sisterhood, flexibility in role playing, respect for elders and strong observation of African tradition and culture.